A Comparative Study on Chemical Composition, Pharmacological Potential and Toxicity of Pogostemon cablin Linn., (Patchouli) Flower and Leaf Essential Oil. Issue 1 (2nd January 2022) - Pandey, Sudin Kumar; Gogoi, Roktim; Bhandari, Sangeeta; Sarma, Neelav; Begum, Twahira; Munda, Sunita; Lal, Mohan
Abstract: Pogostemon cablin Linn., commonly known as patchouli is an aromatic plant with immense use in aroma and perfumery. The purpose of this study was to examine and compare the chemical composition, antimicrobial activity, and various biological activities of Pogostemon cablin Linn flower and leaf essential oils. The compositional analysis was carried out using GC/MS, while standard biological experiments were used to determine the pharmacological potential of both the essential oils. Patchouli alcohol (27.52%, 44.52%) was found to be the major compound followed by caryophyllene (18.23%, 12.86%) for both flowers and leaves essential oil (EO) respectively. P. cablin flower (PCFEO) and leaf essential oil (PCLEO) exhibited weak to strong antimicrobial activities against selected microbial strains. The mitotic index for flower and leaf EO was 14.38% and 15.20% respectively. PCFEO and PCLEO had chromosomal aberrations of 9.0% and 9.60%, respectively. Both PCFEO and PCLEO had substantial antioxidant activity, with PCLEO exhibiting the highest antioxidant activity (IC50 = 1.31 µg/mL). Highest anti-inflammatory activity was exhibited by PCLEO (IC50 = 4.49 µg/mL). Similarly, the anti-diabetic ability of PCLEO (IC50 = 14.19 µg/mL) was greater than the PCFEO (IC50 = 15.60 µg/mL). The PCLEO (IC50 = 7.42 µg/mL) and PCFEO (IC50 = 12.67 µg/mL) both exhibited better anticholinesterase activity than galanthamine (IC50 = 22.16 µg/mL). Better tyrosinase inhibitory activity was shown by PCLEO with IC50 = 4.03 µg/mL than PCFEO IC50 = 4.44 µg/mL. Apart from their antimicrobial activity, the PCLEO was found to outperform both PCFEO as well as the standards in their respective assays. Thus, the present study affirmed the wide application aspects of patchouli essential oil apart from its aromatic application.